Before and During COVID-19: Far-Reaching Transformation of Virtual Reference Services in Academic Library - Norhidayu MD YATIM; Intan Nurbaizura ZAINUDDIN; Noor Faraliza SAMSUDIN; Faddliza MOHD ZAKI; Nurhidayah NASHARUDIN; Jashira JAMIN; Mohd Hafiz KASIRUN (Communications of International Proceedings, 2022)
This paper presents part of a study on virtual references services (VRS) usage trends in an academic library before and during the Covid 19 pandemic.  The data was gathered from the virtual reference services database known as The References Desk Management System (RDMS), developed by the library headquarters.   It presents the findings of four objectives of the study which are to compare the usage of VRS, to identify medium preferred by users before and during the pandemic, to identify type enquiries received before and during pandemic, and subject of the enquiries received by the library before and during the pandemic.In order to answer the research objectives, the data set was categorized into two groups, which is one group to represent the data before the Covid 19 pandemic and another one group to represent data during the Covid 19 pandemic.  Group 1 data covered usage of VRS from the years 2018 until 2019 meanwhile Group 2 covered data from 2020 until 2021. The result highlights there is significant increase of VRS usage by comparing data of virtual references activities. Moreover, it shows positive increasing trend VRS usage thus indicating the different of VRS usage before and during the pandemic
Keywords: Virtual References Services; Covid 19 Pandemic; Academic Library; Library Services